Gangguan Muskuloskeletal di kalangan Pengguna Terminal Paparan Visual di Universiti Malaysia Sarawak Sarawak - Ainin Afizah, Parnon (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This research is to identify symptoms of musculoskeletal disorder among visual display terminal users resulting from. The risk factors examined in this research are visual display terminal, task duration, job duration and age. The sample consist of 50 respondents who are lecturers and supporting staff who are assigned personal visual display terminals at UNIMAS. Data was collected using questionnaires and documentation to identify the related risk factors of musculoskeletal disorder on locomotive organs. The data collected was analyzed using the Statistical Package for Social Sciences version 11.5. Descriptive statistics were used to describe the general details, characteristics and complaints of respondents related to the risk . factors. Correlation analysis was used to determine the relationships between the risk. factors and work and workstation design. The results obtained indicated that though symptoms exist at certain part of locomotive organ such as neck, shoulder, lower and middle of lumbar, elbow, hand, wrist, knee, legs, buttocks, and ankle, the level is still negligible. This could be due to the fact that musculoskeletal disorder is a long-term effect of these symptoms and respondent 's task duration. Therefore it is hoped that the finding of this research will help the management of UNIMAS to look into the design of workstation as an early prevention UNIMAS